VENTURE MANAGEMENT OF BUDGET FUNDS AS A FINANCIAL-LEGAL MEANS OF PROVIDING THE BALANCED BUDGETING SYSTEM OF THE RUSSIAN FEDERATION - E. A. Bochkareva (Russian Journal of Economics and Law)
The article deals with the issue of improving the means of providing the balanced budget system of the Russian Federation. To use the advantages of venture programs, and improve the procedures of their elaboration, it is suggested to use the new method of budget resources management – the venture management method. The necessity to adopt the Federal Law draft “On venture programs” is proved .